The Curricular Practice of a Work-Competency Model for Adult Higher Education - Etty Haydeé Estévez; Luz Delia Acedo Félix; María Guadalupe Bojórquez Ramírez; Beatriz Eugenia Corona Martínez; Carmen Virginia García Acosta; Miguel Ángel Guerrero Badilla; Graciela Guillén Álvarez; Bertha Alicia Loroña García; Jesús Enrique Mungarro Matus; Hisa Margarita Tirado Hamasaki (Universidad Autónoma de Baja California, 2003)
The purpose of this research was to get to know the true curriculum of the Northwestern University's Get Ahead, a special undergraduate program based on the work competencies model and aimed at adults already in the workforce. The goal was to back up the curricular improvement of an educational alternative unique of its kind in Sonora (Mexico). The methodology of Estevez and Fimbres (1998) was used for the formal curriculum analysis and its comparison with the real curriculum from the perspective of its protagonists: teachers and students. The curriculum's internal and external sources were analyzed in order to define the instruments and variables, and to interpret the results. We concluded that the teachers showed that the teachers were more up to date than the students in regard to disciplinary topics. However, they lack adequate teaching strategies to make an impact on students' learning process. Moreover, neither teachers nor students are familiar with the competence model, nor do teachers apply a diagnostic examination to determine their students' competency at the beginning of the course. This indicates that the formal curriculum is distant from the real curriculum.